Development of a Numerical Model for an Expanding Tube with Linear Explosive Using AUTODYN - Mijin Choi; Jung-Ryul Lee; Cheol-Won Kong (Shock and Vibration)
Pyrotechnic devices have been employed in satellite launch vehicle missions, generally for the separation of structural subsystems such as stage and satellite separation. Expanding tubes are linear explosives enclosed by an oval steel tube and have been widely used for pyrotechnic joint separation systems. A numerical model is proposed for the prediction of the proper load of an expanding tube using a nonlinear dynamic analysis code, AUTODYN 2D and 3D. To compute a proper core load, numerical models of the open-ended steel tube and mild detonating tube encasing a high explosive were developed and compared with experimental results. 2D and 3D computational results showed good correlation with ballistic test results. The model will provide more flexibility in expanding tube design, leading to economic benefits in the overall expanding tube development procedure.